2017
DOI: 10.1155/2017/9853439
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Corona Discharge Model and Its Application on Simulating Corona Discharge in the Presence of Wind

Abstract: To evaluate the effect of wind on corona discharges occurring on the tip of a grounded rod during a negative charging process of thundercloud, a two-dimensional numerical model has been improved by considering the wind velocity as a driving force for the movement of the corona charges. It was found that not only wind speed but also wind direction have a significant effect on the distribution of corona charges, the local electric field around the rod, and the corona current. (1) Under the same wind speed, a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…where ϕ is the node potential column vector, K ε is the finite element coefficient matrix of medium permittivity, and K γ is the finite element coefficient matrix of conductivity [23]. Based on these equations, a model of the stator bar end was constructed in COMSOL in order to calculate the electric field and loss distribution at each point.…”
Section: Finite Element Analysis Of the Electric Fieldmentioning
confidence: 99%
“…where ϕ is the node potential column vector, K ε is the finite element coefficient matrix of medium permittivity, and K γ is the finite element coefficient matrix of conductivity [23]. Based on these equations, a model of the stator bar end was constructed in COMSOL in order to calculate the electric field and loss distribution at each point.…”
Section: Finite Element Analysis Of the Electric Fieldmentioning
confidence: 99%
“…For multiple tips, Bazelyan et al [22,24] found that the height of a single tip and the distance between the tips determined the environmental threshold of corona initiation. Using a two-dimensional (2D) time-dependent CD model, Guo et al [25,26] discussed the CD characteristics of a double-needle system with unequal height. Using a three-dimensional (3D) CD model, Guo et al [25] studied the effect of wind on the CD of a single building, but their model did not consider two or more buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, based on the 2D uniform-grid double-needle CD model of Guo et al [25,26] and the 3D independent-needle CD model of Guo et al [27], a 3D variable-grid doubleneedle CD model is established to: (i) study the characteristics of CD between two buildings of equal height and variable separation; and (ii) evaluate the shielding effect of an equal-height building system on the ground electric field by comparing the cases with and without CD.…”
Section: Introductionmentioning
confidence: 99%
“…e frequent collision between gas molecules and electrons or ions causes the change of discharge path and space charge, and the gas discharge model in the flowing gases environment was established. Guo et al [30] improved a two-dimensional numerical model by considering the effect of wind velocity and wind direction on the movement of the corona charges. However, the dielectric breakdown process in strong wind-sand environment is the comprehensive effects of airflow and sand particles.…”
Section: Introductionmentioning
confidence: 99%